Methodology of Problems Creation and Selection for Astronomy Olympiads on Example of Tasks on the Topic of Kepler’s Laws - Ersteniuk, Yaroslav; Gasyuk, Ivan; Boryschak, Anna; Yakubovskyi, Petro (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Based on many years of experience in the organization of the third stage of Ukrainian National Astronomy Olympiad, the authors of the article attempt to formulate general principles for the selection and compilation of astronomy olympiad problems, as well as to demonstrate the application of the described principles on the example of astronomy olympiads in Ivano-Frankivsk region. The peculiarities of school Olympiad in astronomy, the purpose of their conduct, the specificity of task packages, including necessity for differentiation by complexity and topics, were analyzed. A characteristic feature of the Olympiad tasks is their non-standard nature, necessity to use methods that are unusual for students to solve problems. On the other hand, such tasks should match intellectual development of the competition participants, and the course of the solution should be accessible to understanding and should not require knowledge of a university program. In particular, on the basis of the analysis by the authors of the process of compiling astronomy Olympiad tasks, which were offered to students in the past years at the regional stage of the student Olympiads, were identified, the methods of their creation were systematized and characterized. Each method contains a detailed explanation, justification for its use and examples, both analytical and practical. For the sake of clarity, the topic “Kepler Laws” was choosen for Olympiad problems, which were analyzed and methods used to create them were described. This topic is one of the fundamental in the schoolar astronomy, which determines both the need to include such tasks in the Olympiad program and the complexity of their choice, and creation, because the topic is narrow enough and is qualitatively covered in various textbooks and collections of problems.